Out of the trenches; prevalence of Australian veterans among the homeless population and the implications for public health - Lisa Wood; Paul Flatau; Ami Seivwright; Nicholas Wood (Elsevier, 2022)
Abstract Objectives: To examine the prevalence of Australian Defence Force veterans among people sleeping rough and explore their health and social needs relative to non‐veteran rough sleepers. Method: Analysis of responses to the Vulnerability Index - Service Prioritisation Decision Assistance Tool (VI‐SPDAT) collected from 8,027 rough sleepers across five Australian States from 2010‐2017. Results: Veterans were found to comprise 5.6% of people sleeping rough in Australia, with veterans reporting having spent an average of 6.3 years on the street or in emergency accommodation (compared with an average of five years for their non‐veterans counterparts). Veterans had a higher prevalence of self‐reported physical health, mental health and social issues compared with non‐veteran rough sleepers. Conclusions: This is the first study of its kind to elucidate the presence of Australian veterans among people sleeping rough. That they are likely to have spent more years on the street, and have a higher prevalence of health and social issues, highlights the imperative for earlier intervention and prevention of veteran homelessness itself, and its health impacts. Implications for public health: Veteran homelessness has been comparatively hidden in Australia compared to other countries, and consequently the myriad of health, psychosocial and adjustment issues faced by homeless veterans has also been hidden. With heightened attention on veteran suicide and self‐harm, earlier intervention to prevent veterans becoming homeless constitutes sound public health prevention and mental health policy.